Dickkopf 3 promotes the differentiation of a rostrolateral midbrain dopaminergic neuronal subset in vivo and from pluripotent stem cells in vitro in the mouse - Fukusumi, Yoshiyasu; Niehrs, Christof (The journal of neuroscience, 2015)
Wingless-related MMTV integration site 1 (WNT1)/β-catenin signaling plays a crucial role in the generation of mesodiencephalic dopaminergic (mdDA) neurons, including the substantia nigra pars compacta (SNc) subpopulation that preferentially degenerates in Parkinson's disease (PD). However, the precise functions of WNT1/β-catenin signaling in this context remain unknown. Stem cell-based regenerative (transplantation) therapies for PD have not been implemented widely in the clinical context, among other reasons because of the heterogeneity and incomplete differentiation of the transplanted cells. This might result in tumor formation and poor integration of the transplanted cells into the dopaminergic circuitry of the brain. Dickkopf 3 (DKK3) is a secreted glycoprotein implicated in the modulation of WNT/β-catenin signaling. Using mutant mice, primary ventral midbrain cells, and pluripotent stem cells, we show that DKK3 is necessary and sufficient for the correct differentiation of a rostrolateral mdDA neuron subset. Dkk3 transcription in the murine ventral midbrain coincides with the onset of mdDA neurogenesis and is required for the activation and/or maintenance of LMX1A (LIM homeobox transcription factor 1α) and PITX3 (paired-like homeodomain transcription factor 3) expression in the corresponding mdDA precursor subset, without affecting the proliferation or specification of their progenitors. Notably, the treatment of differentiating pluripotent stem cells with recombinant DKK3 and WNT1 proteins also increases the proportion of mdDA neurons with molecular SNc DA cell characteristics in these cultures. The specific effects of DKK3 on the differentiation of rostrolateral mdDA neurons in the murine ventral midbrain, together with its known prosurvival and anti-tumorigenic properties, make it a good candidate for the improvement of regenerative and neuroprotective strategies in the treatment of PD. - SIGNIFICANCE STATEMENT We show here that Dickkopf 3 (DKK3), a secreted modulator of WNT (Wingless-related MMTV integration site)/β-catenin signaling, is both necessary and sufficient for the proper differentiation and survival of a rostrolateral (parabrachial pigmented nucleus and dorsomedial substantia nigra pars compacta) mesodiencephalic dopaminergic neuron subset, using Dkk3 mutant mice and murine primary ventral midbrain and pluripotent stem cells. The progressive loss of these dopamine-producing mesodiencephalic neurons is a hallmark of human Parkinson's disease, which can up to now not be halted by clinical treatments of this disease. Thus, the soluble DKK3 protein might be a promising new agent for the improvement of current protocols for the directed differentiation of pluripotent and multipotent stem cells into mesodiencephalic dopaminergic neurons and for the promotion of their survival in situ.
Gesehen am 06.08.2021